Bovine And Human Zona Pellucida 3 Gene Glycans Site Prediction Using In Silico Analysis - Mubarakati, Nurul Jadid; Aulanni'am, Aulanni'am; Sumitro, Sutiman Bambang; Ciptadi, Gatot (Journal of Tropical Life Science, 2014)
Zona pellucida is one of the protective layer of the egg cell and has a function as an intermediary species-specific fertilization. Glycoproteins of human and bovine zona pellucida is composed of three types, namely ZP1, ZP2 and ZP3. ZP3 gene has amino acid sequence homology with other mammals. Oligosaccharides components of the zona pellucida glycans are composed from units of asparagine residues (N -linked) and serine/threonine (O -linked). The aims of this study was to analyze the DNA sequences of human and bovine and further predicts glycans site on amino acid sequence of human and bovine ZP3. In this study, ZP3 gene fragments have been isolated from bovine and humans were analyzed in Silico. This work were conducted by comparing the data of DNA sequence from human and bovine PCR product using NCBI BLAST. The results showed that there were similarities at amino acid positions number 23-38. bZP3 sequence had three glycans site (Asn-X-Thr/Ser) and one site on hZP3 glycans. One of the sites was conserved between the two species.